Direct and indirect effects of father-child attachment on academic burnout in college students - Zhang, Zhenyun; Wang, Yuhua; Wu, Huifen; Zhou, Yuqin; Peng, Cong (Frontiers in Psychology, 2024)
The study aims to investigate the multiple mediating roles of core self-evaluation and sense of school belonging in the relationship between father-child attachment and academic burnout in college students. A sample of 418 college students completed the father-child attachment scale, the scale of sense of school belonging, core self-evaluation scale, and academic burnout scale. After controlling for variables such as mother–child attachment, gender, age, and grade, the results showed: (1) father-child attachment was significantly and negatively correlated with academic burnout, and positively correlated with core self-evaluation and sense of school belonging; both core self-evaluation and sense of school belonging were significantly and negatively correlated with academic burnout. (2) The multiple mediating model of father-child attachment influencing academic burnout in college students was established. Both core self-evaluation and sense of school belonging played a partial mediating role between father-child attachment and academic burnout. The direct effect of father-child attachment on academic burnout accounts for 33.3% of the total effect. The indirect effects of core self-evaluation and sense of school belonging between father-child attachment and academic burnout account for 50.0 and 16.7% of the total effect, respectively. These findings identify the internal mechanisms through which father-child attachment affects academic burnout in college students from personal traits and interpersonal perspectives.